2010
DOI: 10.5771/0935-9915-2010-2-193
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation in Innovation Networks: The Case of Danish and German SMEs

Abstract: Information is a critical resource in innovation processes. External information can be helpful in innovation processes to complete them successfully. SMEs in particular are therefore advised to draw on consulting in innovation processes, as they cannot ensure the necessary information flow internally due to the lesser resources they have compared to larger companies. To promote economically relevant information of SMEs, the public sector provides specific advisory services. These services, however, are rarely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…Filieri et al (2014) found that bonding actors leveraged the process of network formation before cohesion was observable. Especially, actorssuch as consultantsstep in the role as mediators and can compensate missing strong ties and/or inspire the aspiring entrepreneurs with new ideas (Gretzinger et al, 2010). This is in line with Sørensen (2016) who recommends for rural areas a stronger support of relationships among communities to trigger the use of weak ties.…”
Section: Strong Ties Weak Ties and Deduction Of Marketable Solutionssupporting
confidence: 55%
See 2 more Smart Citations
“…Filieri et al (2014) found that bonding actors leveraged the process of network formation before cohesion was observable. Especially, actorssuch as consultantsstep in the role as mediators and can compensate missing strong ties and/or inspire the aspiring entrepreneurs with new ideas (Gretzinger et al, 2010). This is in line with Sørensen (2016) who recommends for rural areas a stronger support of relationships among communities to trigger the use of weak ties.…”
Section: Strong Ties Weak Ties and Deduction Of Marketable Solutionssupporting
confidence: 55%
“…This is in line with our model. Even if consultants are viewed from their customer's viewpoint as weak ties (Gretzinger et al, 2010), they can be used by aspiring entrepreneurs to leverage the process of (business and customer) network formation. Owing to their bridging function, they can support aspiring entrepreneurs in accessing complementing resources and acquiring new business partners and customers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these interactions among members of the same profession institute and reinforce practices which are held to be acceptable and legitimate within the given profession. This results in homogeneous perceptions, behaviours and practices in the form of normative isomorphism [28]. In line with normative isomorphism, a study by Gretzinger et al [29] found that SMEs in Denmark and Germany utilised professional consultancy and cooperated with their counterparts in developing new products.…”
Section: Normative Configurationmentioning
confidence: 93%
“…According to Bourdieu (1972), social fields represent competitive arenas or networks in which agents use various resources and strategies compatible with field‐specific rules, to occupy positions that provide a relative advantage in relation to other agents, in terms of practices of what one can do, and capital maximisation (Walter, 2014). Bourdieu (1986) distinguishes four types of capital: (i) economic – a person's fortune and revenues; (ii) cultural – education, experiences and attained learning resulting in specific intellectual capabilities and qualifications; (iii) social – a person's social relations that allow access to material and immaterial resources (Gretzinger et al ., 2010); and (iv) symbolic – an individual's legitimacy or credibility, as social recognition of his/her economic, social, and cultural capital. All forms of capital are interdependent and can be ultimately converted into symbolic capital (Bourdieu, 1972).…”
Section: Definitionmentioning
confidence: 99%